Penapisan Senyawa Bioaktif Antimikroba dari Ekstrak Campuran Daun Inggu (Ruta angustifolia L.) dan Bakteri Endofit Pseudomonas azotoformans UICC B-91 sebagai Sediaan Oral Nutraceutical - Mohammad Ananda Reza Kurniawan; Rina Hidayati Pratiwi; Fika Arie Susanti (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The oral cavity as a passageway for various types of substances can be a nesting place for various types of microbes that can cause microbial infections, including candidiasis. Inggu leaf extract and extract of the endophytic bacteria Pseudomonas azotoformans in previous studies have shown the resulting antimicrobial activity. The aim of the study was to screen for antimicrobial bioactive compounds from inggu leaf extract and endophytic bacteria as nutraceutical oral preparations. A mouthwash formulation was made with the addition of crude extract of inggu leaves and pure extract of the endophytic bacteria Pseudomonas azotoformans as antimicrobial agents. The method used is laboratory experimental. The formulation was made by adding the crude extract of inggu leaves and pure extract of the endophytic bacteria Pseudomonas azotoformans and divided into 3 formulations A, B, and C with a ratio of 1:1, 1:2, and 2:1 respectively. The results showed that each mouthwash preparation had an inhibition zone on preparations A, B and C, which were 8.55 mm; 8.55mm; and 9.53mm. The normality test result for each preparation was 0.05. The homogeneity test results obtained a significance value of 0.074 (p > 0.05). The results of the one way ANOVA test found a significance value of 0.000 (p <0.05), there was a significant difference in the variation in the concentration of the mouthwash formula in inhibiting the growth of the Candida albicans fungus. The inhibition zone formed indicated the presence of antimicrobial activity from the mouthwash and all formulas were included in the moderate criteria according to the Davis & Stout method. All preparations are homogeneous because there is no precipitate, have the dominant smell and color of inggu leaves, and have a sweet taste that is slightly mixed with bitter and spicy from inggu leaves.